Is an en-commandite partnership a tax-efficient vehicle in the current private equity regime with the focus on Investments in South Africa? - Ueckermann, Francois (Department of Finance and Tax, 2023)
Private equity (PE) firms often use different investment vehicles to attract high-net-worth individuals and institutional investors to invest with them, as after-tax returns are generally higher than the formal investment sector. A question that arose during a discussion with the head of tax of a large insurance company was: Is an en-commandite partnership a taxefficient vehicle in the current private equity regime? The purpose of this dissertation is to determine whether the benefits of en-commandite partnership outweighed other forms of investment vehicles with regard to flow-through of income. It also dealt with the elimination of entity-level tax, while protecting investors from personal liability for the debts and obligations of the fund. This paper firstly investigated the characteristics of the most common investment vehicles, and the legislative requirements that they are subjected to. Secondly, the tax regime that applies to these investment vehicles was investigated. It included the financial instruments used by PE firms and how different applications of these instruments are treated by the tax authorities. This was done to determine if, when, and how these instruments were taxed as income or capital, and in whose hands they were taxed. This also covered the potential pitfalls PE firms had to be aware of when structuring investment transactions. This was followed by a conclusion to the question: Is an encommandite partnership a tax-efficient vehicle in the current private equity regime with the focus on investments in South Africa? The study includes a comparative analysis of the legislative and tax consequences of the investment vehicles as well as the benefits that could be derived from each. High-net-worth individuals and institutional investors often seek investment opportunities where they are prepared to take a higher investment risk with the objective to achieve a higher return on their investments. They can either invest in ventures and manage the investments themselves, or they can use PE firms to take up shares in private or unlisted companies to manage investments on their behalf. Confidentiality of financial affairs of individuals in particular, favour PE firms that use trusts and partnerships as investment ii vehicles, as legislative disclosure requirements are very limited. In an en commandite partnership, the identity of limited partners is not disclosed. The most important considerations for investors are to maximise the after-tax return on their investments and to limit their potential liability and exposure to debts. With the current structure of PE firms and their professional oversight in the management of the underlying investments under their control, it is submitted that an en commandite partnership is the most tax-efficient vehicle in the current private equity regime. This is primarily due to the conduit principle, where taxation at fund level is averted, and the tax liability passesthrough to investors with differing tax structures. The Capital Gains Tax (CGT) inclusion rate is also the lowest for individuals when utilising an en commandite partnership. PE firms focus on maximising investment returns within the constraints of tax legislation and investors take care of their own tax affairs.